Analisis Keputusan Pemilihan Penggunaan Obat Herbal dan Obat Konvensional di Kalangan Usia Produktif Kecamatan Pangkah - Listina, Osie; Khoirunnisa, Dhea Ayu; Alfiraza, Ery Nourika (Department of Pharmacy, Bumigora University, 2025)
Herbal medicine and conventional medicine are two primary treatment options commonly used by the productive age population in addressing health issues. This study aims to determine the percentage of medicine preference, the dominant factors influencing decision-making, as well as the knowledge of medicinal plants and attitudes of the productive age community toward the use of herbal and conventional medicines. The research employed a mixed-methods using questionnaires and interviews through stratified random sampling. The results showed that 61% of respondents preferred conventional medicine, while 39% chose herbal medicine. The dominant factor influencing the use of herbal medicine was its minimal side effects, whereas the main reason for choosing conventional medicine was its effectiveness in treating diseases. Descriptive analysis concluded that the productive age population tends to prefer conventional medicine over herbal medicine for daily treatment.